The Effects of Probiotic and Zinc on Hemoglobin Levels in Malnourished Rats - Perez Wahyu Purnasari; Citra Primavita Mayangsari; Conita Yuniarifa (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackgrounds:Iron supplementation has not been able to maximize the reduction of anemia in children. Iron consumption that is not sufficient for daily needs and low iron absorption and lack of diversity of food sources of iron are the main causes of anemia in children. The absorption ability of macro and micro-nutrients is strongly influenced by the histological features of the ileum. Improvements in the histological features of the ileum by administering probiotics and zinc in cases of malnutrition are expected to improve absorption function, so that absorption of nutrients, especially iron, can be betterObjectives: To assess the effect of probiotics and zinc on hemoglobin levels in malnourished rats.Methods: The experimental study, using 30 rats aged 8 weeks, body weight 180-200 g, divided randomly into 5 groups. Group N was given a standard diet, groups M, PZ, P, and Z were given a low calorie diet for 14 days to make malnourished. The treatment was started on day 15 to 28, group M was still given a low calorie diet, groups PZ, P, and Z were given a standard diet and supplementation. PZ group was given a combination of probiotics and zinc, P group was given probiotics, and Z group was given zinc. On the 29th day, all blood samples were checked for Hb levels using spectrophotometry.Results:There was a significant difference in hemoglobin levels between the malnourished group and the treatment group (p < 0.0001). Hemoglobin levels in probiotic group were significantly higher among the other treatment groups and the combination group indicated significantly lower hemoglobin levels.Conclusions: Probiotic and zinc administration significantly influence hemoglobin levels in malnourished rats.